2020
DOI: 10.1021/acs.jpcc.0c09967
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Neutron Powder Diffraction Study of ε-CL-20: A Gentler Way to Study Energetic Materials

Abstract: High-pressure studies have been performed on the ε-form of the powerful explosive CL-20. Hydrostatic compression over the pressure range 0-12 GPa has been monitored using synchrotron powder X-ray diffraction. The potential effects of X-ray radiation damage were observed and circumvented through a follow-up compression study over the pressure range 0-7 GPa using neutron powder diffraction. This second study revealed smooth compression behaviour, and the absence of any phase transitions. Intermolecular interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…Metal-organic frameworks and coordination polymers principally show reductions in volume upon X-ray radiation damage, which may be linked to their amorphization process. However, in the case of molecular compounds, an increase in volume is more typically observed with increasing X-ray irradiation, as measured for Br(collidine) 2 ClO 4 glycinium phosphite, the energetic molecule 2,4,6,8,10,12-hexanitrohexaazaisowurtzitane and [M(1,5-cyclooctadiene)Cl] 2 catalysts with M = Ir + or Rh + (Morgan et al, 2018;Bogdanov et al, 2021;Konar et al, 2020;Fernando et al, 2021). The impact of radiation on structural behaviour is again highlighted for Br(collidine) 2 ClO 4 , where diffuse scattering disappears upon increased X-ray exposure (Morgan et al, 2018).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Metal-organic frameworks and coordination polymers principally show reductions in volume upon X-ray radiation damage, which may be linked to their amorphization process. However, in the case of molecular compounds, an increase in volume is more typically observed with increasing X-ray irradiation, as measured for Br(collidine) 2 ClO 4 glycinium phosphite, the energetic molecule 2,4,6,8,10,12-hexanitrohexaazaisowurtzitane and [M(1,5-cyclooctadiene)Cl] 2 catalysts with M = Ir + or Rh + (Morgan et al, 2018;Bogdanov et al, 2021;Konar et al, 2020;Fernando et al, 2021). The impact of radiation on structural behaviour is again highlighted for Br(collidine) 2 ClO 4 , where diffuse scattering disappears upon increased X-ray exposure (Morgan et al, 2018).…”
Section: Introductionmentioning
confidence: 89%
“…With the increasing use of third-and fourth-generation synchrotrons, the impact of radiation damage in small-molecule crystallographic research has gained greater importance (Christensen et al, 2019). Radiation damage is especially critical for in-situ and time-resolved studies, where the sample is investigated as a function of various external conditions, and is measured multiple times (Konar et al, 2020). It then becomes important to separate the possible effects from exposure to X-ray irradiation and the behaviour of the sample due to the applied stimulus, such as temperature or pressure.…”
Section: Introductionmentioning
confidence: 99%
“…26 The continued validation of increasingly sophisticated dispersion models has demonstrated that the DFT plus dispersion (DFT-D) model not only can reproduce experimentally determined hydrostatic compression behavior but can also be used to guide experimental endeavors. 25 The objectives of this research effort were therefore as follows: (i) to perform the first high-pressure neutron diffraction study on perdeuterated p-xylene to solve the highpressure phase, (ii) to reproduce the pressure-induced crystallization on hydrogenous p-xylene inside a DAC and to compare the high-pressure single-crystal structure with the neutron powder data; (iii) to explore the ability of modern DFT models to predict the hydrostatic compression behavior, and (iv) to obtain accurate pressure−volume equations of state.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been shown that neutron techniques cause much less radiation damage for molecular materials. 24,25 To further complement our experimental findings, we performed first-principles simulation as well. Density functional theory (DFT) has demonstrated a remarkable ability to predict the evolution of structures with pressure, particularly when weak dispersion forces are accounted for.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation